Impediments to agricultural development in small scale farms: a case of Nyazvidzi small scale farming area in Zimbabwe - Mahuni, Brian (Midlands State University, 2014)
The study serves to provide an assessment of impediments to agricultural development in Nyazvidzi small scale farming area with special attention being placed upon the relationships between the farmers and all agricultural stakeholders whom they interact with, rural livelihoods systems, infrastructure, the natural environment, agricultural production and marketing. The information was gathered and analyzed using both quantitative and qualitative research methods. The target sample for quantitative approach was the farmers alone while qualitative participants included farmers, community leaders and government workers from AGRITEX and veterinary departments. The first chapter of the study covers the background to the study while chapter two provides the reviewed literature on impediments to agricultural development and general solutions and theoretical framework of the study. Chapter three presents the research methodology used in the study and chapter four covers data analysis and presentation. The fifth chapter provides main conclusion as well as indicated action. Amongst the main impediments found from the research included, lack of farming inputs, poor road network and market accessibility, unpredictable weather patterns, shortage of labor force, animal and crop diseases, wild animals that destroy crops and livestock as well as lack of education. From the conclusion and recommendations the research findings indicated that apart from the provision of inputs and improvement of market accessibility, there is need for agricultural stakeholders to put much focus on the development of the farmers so that they can be able to understand their changing environment and develop skills on how to deal with it and increase their production.